Growth in Hyper-Concentrated Sweet Whey Triggers Multi Stress Tolerance and Spray Drying Survival in Lactobacillus casei BL23: From the Molecular Basis to New Perspectives for Sustainable Probiotic Production - Huang, Song; Gaucher, Floriane; Cauty, Chantal; Jardin, Julien; Le Loir, Yves; Jeantet, Romain; Chen, Xiao Dong; Jan, Gwénaël (Frontiers in Microbiology, 2018)
Lactobacillus casei BL23 has a recognized probiotic potential, which includes immune modulation, protection towards induced colitis, towards induced colon cancer and towards dissemination of pathogens. In L. casei, as well as in other probiotics, both probiotic and technological abilities are highly dependent 1) on the substrate used to grow bacteria and 2) on the process used to dry and store this biomass. Production and storage of probiotics, at a reasonable financial and environmental cost, becomes a crucial challenge. Food-grade media must be used, and minimal process is preferred. In this context, we have developed a “2-in-1” medium used both to grow and to dry L. casei BL23, considered a fragile probiotic strain. This medium consists in hyper-concentrated sweet whey (HCSW). L. casei BL23 grows in HCSW up to 30% dry matter, which is 6 times-concentrated sweet whey. Compared to isotonic sweet whey (5% dry matter), these growth conditions enhanced tolerance of L. casei BL23 towards heat, acid and bile salts stress. HCSW also triggered intracellular accumulation of polyphosphate, of glycogen and of trehalose. A gel-free global proteomic differential analysis further evidenced overexpression of proteins involved in pathways known to participate in stress adaptation, including environmental signal transduction, oxidative and metal defense, DNA repair, protein turnover and repair, carbohydrate, phosphate and amino acid metabolism, and in osmoadaptation. Accordingly, HCSW cultures of L. casei BL23 exhibited enhanced survival upon spray drying, a process known to drastically affect bacterial viability. This work opens new perspectives for sustainable production of dried probiotic lactobacilli, using food industry by-products and lowering energy costs.